Potential of endophytic yeasts as biocontrol of Phytophthora capsici, causative agent of foot rot disease on black pepper - DIAN SAFITRI; SURYO WIYONO; ENDANG DWI PURBAJANTI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Safitri D, Wiyono S, Purbajanti ED. 2023. Potential of endophytic yeasts as biocontrol of Phytophthora capsici, causative agent of foot rot disease on black pepper. Biodiversitas 24: 5847-5853. Phytophthora capsici is the main pathogen of foot rot disease of black pepper. This disease contributes to a significant decrease in black pepper productivity. Conventional disease management strategies usually require the use of chemical pesticides, which can have harmful environmental and human health consequences. Introducing biological agents such as endophytic yeasts for controlling foot rot disease has minimal effect on human health and is sustainable. One technique to control foot rot disease is to use biological agents such as endophytic yeasts. The aim of this research was to find yeast against Phytophthora capsici. The methods used included (i) study development and identification of endophytic yeast and (ii) in vitro and in vivo antagonism screening of yeast against P. capsici. The results showed that 49 endophytic yeasts were isolated from the leaves, fruits and roots of three black pepper lines. Five isolates had selected based on the highest antibiosis in antagonism test by in vitro: END6, END21, END66, END87, and END14. Isolate END87 had a mycelium inhibition rate of 64.55%, and a low level of inhibition was found in isolate 21, which had a mycelium size of 42.81%. The molecular characterization based on the sequence partial of NL1 and NL4. Moreover, 5 isolates of endophytic yeast (END6, END21, END66, END87, and END14) were identified as Rhodotorula mucilaginosa, Hannaella oryzae, Cryptococcus tephrensis.